Yeast Sen1 helicase protects the genome from transcription-associated instability - Mischo, H; Gómez-González, B; Grzechnik, P; Rondón, A; Wei, W; Steinmetz, L; Aguilera, A; Proudfoot, N (Elsevier, 2011)
Sen1 of S.cerevisiae is a known component of the NRD complex implicated in transcription termination on nonpolyadenylated as well as some polyadenylated RNA polymerase II transcripts. We now show that Sen1 helicase possesses a wider function by restricting the occurrence of RNA:DNA hybrids that may naturally form during transcription, when nascent RNA hybridizes to DNA prior to its packaging into RNA protein complexes. These hybrids displace the nontranscribed strand and create R loop structures. Loss of Sen1 results in transient R loop accumulation and so elicits transcription-associated recombination. SEN1 genetically interacts with DNA repair genes, suggesting that R loop resolution requires proteins involved in homologous recombination. Based on these findings, we propose that R loop formation is a frequent event during transcription and a key function of Sen1 is to prevent their accumulation and associated genome instability.